2009
DOI: 10.1159/000197864
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Presynaptic GABA<sub>B</sub> Receptor Function in the Neocortex of a Genetic Model of Absence Epilepsy

Abstract: Changes in GABAB receptor subunit expression have been recently reported in the neocortex of epileptic WAG/Rij rats that are genetically prone to experience absence seizures. These alterations may lead to hyperexcitability by downregulating the function of presynaptic GABAB receptors in neocortical networks as suggested by a reduction in paired-pulse depression. Here, we tested further this hypothesis by analyzing the effects induced by the GABAB receptor agonist baclofen (0.1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…49 Moreover, the Avoli group reported that higher doses of the GABA B agonist baclophen were required to depress pharmacologically isolated, stimulus-induced inhibitory postsynaptic potentials (IPSPS) generated by WAG/Rij neocortical neurons as compared to those recorded from cells from non-epileptic control (NEC) cells. 50 A similar decreased sensitivity became evident when baclophen was tested on the synchronous network-driven IPSPs generated by neocortical slices treated with 4AP + glutamatergic receptor antagonists. 50 An increase of cortical excitation could also predetermine absence seizures in WAG/Rij rats.…”
Section: Neurophysiological Evidencementioning
confidence: 70%
“…49 Moreover, the Avoli group reported that higher doses of the GABA B agonist baclophen were required to depress pharmacologically isolated, stimulus-induced inhibitory postsynaptic potentials (IPSPS) generated by WAG/Rij neocortical neurons as compared to those recorded from cells from non-epileptic control (NEC) cells. 50 A similar decreased sensitivity became evident when baclophen was tested on the synchronous network-driven IPSPs generated by neocortical slices treated with 4AP + glutamatergic receptor antagonists. 50 An increase of cortical excitation could also predetermine absence seizures in WAG/Rij rats.…”
Section: Neurophysiological Evidencementioning
confidence: 70%
“…; Inaba et al . ). Alternatively, the persistent membrane depolarization could be caused by an upregulation of voltage‐gated sodium channels as previously reported (Klein et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, neuronal hyperactivity is associated with plastic changes of CB 1 receptors. Interestingly, symptomatic WAG/Rij rats show an increased expression of type‐4 metabotropic glutamate receptors (mGlu4 receptors) in the RTN (Ngomba et al, 2008), an increased expression of mGlu2/3 receptors in the VBTNs and the somatosensory cortex (Ngomba et al, 2005), and a reduced expression and function of GABA B receptors in the neocortex (Merlo et al, 2007; Inaba et al, 2009). In addition, there was a specific loss of alpha3 subunit protein of the GABA A receptors in the RTN (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%